A novel pathway for the synthesis of inositol phospholipids uses cytidine diphosphate (CDP)‐inositol as donor of the polar head group. (11th February 2015) - Jorge, Carla D.; Borges, Nuno; Santos, Helena
Summary We describe a novel biosynthetic pathway for glycerophosphoinositides in Rhodothermus marinus in which inositol is activated by cytidine triphosphate (CTP); this is unlike all known pathways that involve activation of the lipid group instead. This work was motivated by the detection in the R. marinus genome of a gene with high similarity to CTP:L‐myo‐inositol‐1‐phosphate cytidylyltransferase, the enzyme that synthesizes cytidine diphosphate (CDP)‐inositol, a metabolite only known in the synthesis of di‐myo‐inositol phosphate. However, this solute is absent in R. marinus. The fate of radiolabelled CDP‐inositol was investigated in cell extracts to reveal that radioactive inositol was incorporated into the chloroform‐soluble fraction. Mass spectrometry showed that the major lipid product has a molecular mass of 810 Da and contains inositol phosphate and alkyl chains attached to glycerol by ether bonds. The occurrence of ether‐linked lipids is rare in bacteria and has not been described previously in R. marinus. The relevant synthase was identified by functional expression of the candidate gene in Escherichia coli. The enzyme catalyses the transfer of L‐myo‐inositol‐1‐phosphate from CDP‐inositol to dialkylether glycerol yielding dialkylether glycerophosphoinositol. Database searching showed homologous proteins in two bacterial classes, Sphingobacteria and Alphaproteobacteria. This is the first report of the involvement of CDP‐inositol in phospholipid synthesis.